The Influence of Board of Directors Structure and Ownership Structure on Company Performance - Alfadia, Osa; Budiantoro, Harry; Marhamah, Siti; Lapae, Kanaya; Agus Tantri Ningsih, Hestin (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
This research was conducted with the aim of examining the effect of board of directors structure and ownership structure on company performance. In this study the variables used were the board of directors, board size, female board of directors, constitutional ownership, managerial ownership, foreign ownership as independent variables, and company performance as the dependent variable. This study uses secondary data, namely food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The population in this study were 22 companies. To determine the sample in this study using purposive sampling method. With a sample of 10 companies for 5 periods. The data analysis method in this study uses multiple linear regression. Based on the results of the study it was concluded that independent board of directors and ownership structure have a positive influence on company performance, female board of directors has a negative effect on company performance, board size, managerial ownership and foreign ownership have no effect on company performance.